Unilateral cataract associated with eyelid ash-leaf macule in tuberous sclerosis complex. (15th September 2018) - Selvaraj, Rajalakshmi; Kasturi, Nirupama; Kumari, Pooja; Muraleedharan, Sabreesh
Abstract : A 9-month-old male child with tuberous sclerosis complex presented with ash-leaf macules on the left periocular region and ipsilateral dense cataract. Fundus showed retinal astrocytic hamartomas. This case is reported for unilaterality of congenital cataract on the same side of eyelid ash-leaf macule in tuberous sclerosis.